Effect of intraspecific larval aggregation and diet type on life-history traits of Dermestes maculatus and Dermestes caninus (Coleoptera: Dermestidae): species of forensic importance / Rodrigo C. Corrêa ... [et al.] - Corrêa, Rodrigo C.; Carmo, Rodrigo R.F; George, Ann R.; Tomberlin, Jeffery K. (Faculty of Medicine, 2021)
Introduction: Numerous studies have examined the effect of abiotic factors on the development and survival of Dermestes and their importance for forensic entomology. Dermestes maculatus is one of the most known beetle species associated with corpses and D. caninus has little biological information available and no case report records. To better understand the life-history traits of those species we evaluated the impact of diet type and intraspecific larval density. Methods: Adult beetles were collected from human remains and colonies were kept under controlled conditions (27.0 ± 1.0 °C, 55.0% RU, and 12:12 L:D) and F 1 generation was used to collect eggs. Newly emerged larvae were separated according to the treatments, being the combination of larval density (1, 15, 30 individuals), food (dried dog food or dried pork) and contact (with or without). We used factorial-ANOVA to test the individual and combined effect of both larval densities and diet on dependent variables, followed by post-hoc Tukey test. Pearson correlations were carried out to evaluate the relationship between larval parameters for each species in each treatment. Results: Porkbased diet positively affected species fitness, with larvae being ca. 1.1 (D. caninus) and 1.7 (D. maculatus) times bigger and heavier than in dog food. Diet type also impacted the development time for both species. Conclusions: Data generated through the current study serve as a foundation for potential application of this species as an indicator of time of colonization in relations to a minPMI. However, validation is still needed to determine the accuracy and precision of these calculations.